Validity Canva Video Media Integrated Thematic Learning Based On PBL Models In Elementary Schools - Chintya Nefillia Alwi Dalimunthe; Reinita Reinita (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
Canva is an online application that is used in the creation of learning media. The purpose of this study is to develop Canva Video media on integrated thematic learning based on the Problem Based Learning (PBL) model in grade IV of a valid elementary school. The type of research carried out is Research ang Development (R&D) with a 4D development model, namely Define, Design, Develop, and Disseminate. This research was conducted in elementary schools by collecting data techniques using questionnaires from material experts, linguists, and media experts. The test subjects in this study were 32 grade IV students of SDN 19 Ambacang Anggang and SDN 11 Tanjung Alai. The results of the Canva Video Media development research developed obtained material validity test results of 91.6%, language validity test results of 87.5%, and media validity test results of 100%. Thus it can be concluded that Canva Video Media on integrated thematic learning in grade IV Elementary School has been validly used.